Impact of Veterinary Herd Health Management on German Dairy Farms: Effect of Participation on Farm Performance - Ries, Jenny; Jensen, Katharina Charlotte; Müller, Kerstin Elisabeth; Thöne-Reineke, Christa; Merle, Roswitha (Frontiers in Veterinary Science, 2022)
German dairy farming has intensified markedly in recent years and the demand for veterinary herd health management (VHHM) is rising. To protect farms from epidemics, ensure food safety and prevent developing of antibiotic resistance, VHHM has been anchored in EU law since April 2021. Via an online survey, distributed by different farmer’s organizations, dairy farmers were asked about the cooperation with their veterinarian. The aim was to evaluate farm performance as a function of participation in VHHM. From 216 analyzed questionnaires, 106 respondents participated in VHHM. Results showed that farmers, who make use of VHHM and consult their veterinarian in decision-making frequently, have the highest 305-day milk yield (305dMY), the lowest bulk tank somatic cell counts (BTSCC) and the lowest age at first calving (AFC). However, these farmers tended to have higher replacement rates (RR) and a higher mortality of cows in the period up to 60 days in milk (MORT60DIM). Furthermore, respondents who defined VHHM as “evaluation of herd data, strategic planning” had the highest 305dMY compared to those who defined VHHM through one of the different options given (“pregnancy checks & support in reproduction” / “problemsolving”). In the multifactorial regression model, VHHM participating farms had a 660 kg higher 305dMY and one month less in AFC, compared to farms not participating in VHHM. However, within the VHHM participants, no association between VHHM practices and performance parameters was found. Further research is needed, to find out if tailored advice of the VHHM approach may show effect herein.